FRI0400 Efficacy of anakinra in calcium pyrophosphate crystal arthritis. (23rd January 2014) - Ottaviani, S.; Brunier, L.; Sibilia, J.; Maurier, F.; Dawidowicz, K.; Palazzo, E.; Hayem, G.; Ardizzone, M.; Wendling, D.; Meyer, O.; Dieudé, P.
Abstract : Background: Calcium pyrophosphate (CPP) associated arthritis is common in elderly patients. Non-steroidal anti-inflammatory drugs (NSAID), colchicine, oral or local steroids are recommended (1), but in some patients these therapies are non-effective or contra-indicated and therapeutic alternatives are limited. Recently, the pivotal role of IL-1β in the crystal-induced inflammation has been demonstrated, and IL-1β inhibitors such as anakinra, has been shown to be effective in the treatment of acute gout arthritis (2). Objectives: To evaluate the efficacy of anakinra on refractory CPP arthritis. Methods: In a multicentric retrospective study, patients having proven acute or chronic CPP arthritis by CPP crystal demonstration in synovial fluid or typical X-rays were included. All the patients had failure or contra-indication to conventional therapies and received subcutaneous anakinra (100mg/day). All individuals provided informed written consent as approved by the recruiting site institutional review boards at each of the affiliate institutions. Ultrasonographic assessment, measure of pain by Visual Analogic Scale (0-100 mm VAS pain), CRP level and consummation of corticosteroids were assessed at baseline and at day 4. Results: A total of 16 patients were included in this open study. Mean age was 80.2±11.1 year-old and mean symptoms duration was 3.9±3.8 months. Arthritis was localized to wrists (n=15, 88%), shoulders (n=12, 71%), knees (n=11, 65%), ankles (n=11, 59%), elbows (n=7, 47%), cervical spine (n=7, 41%), tarsal joints (n=6, 29%) and MCPs (n=4, 24%). Between baseline and day 4, IL-1β blockade led to a significant decrease of VAS pain (76.6±12.3 to 33.0±14.5 mm; P<0.0001) and CRP level (97.3±57.4 to 20.0±15.2 mg/l; P<0.0001). The consummation of corticosteroids between baseline and day 4 decreased from 22.8±7.5 mg/day to 5.2 mg ± 4.2 (P<0.0005). Relapse occurred in 6 patients (mean delay of relapse: 3.3±4.5 months) and infectious complication (uncomplicated pyocyanic pneumonitis) was noted in one patient 3 weeks after the IL-1β blockade was stopped. Conclusions: Anakinra is an effective and relatively well-tolerated treatment of refractory CPP arthritis and should be an alternative in individuals having non-response or contra-indication to conventional therapies. References: Zhang W, Doherty M, Pascual E, Barskova V, Guerne PA, Jansen TL, et al. EULAR recommendations for calcium pyrophosphate deposition. Part II: management. Ann Rheum Dis 2011;70(4):571-5. So A, De Smedt T, Revaz S, Tschopp J. A pilot study of IL-1 inhibition by anakinra in acute gout. Arthritis Res Ther 2007;9(2):R28. Disclosure of Interest: None Declared